High-toughness ZrNbTa-based refractory high-entropy alloy and preparation method thereof
By optimizing the composition and microstructure of ZrNbTa-based high-entropy alloy, the problem of insufficient deformation ability of refractory high-entropy alloys at room temperature is solved, and the high yield strength and uniform elongation are improved, which is suitable for applications in high-temperature environments.
Patent Information
- Application Number
- CN202411326961.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-23
AI Technical Summary
Refractory high entropy alloys lack uniform deformation ability at room temperature, and the yield strength of existing ZrHfVNbTa alloys is low, which limits its application.
By optimizing the composition of ZrNbTa-based high-entropy alloy, modulus mismatch is achieved and the microstructure structure is regulated, a dual BCC structure is obtained, and combined with the insulation treatment of the high-temperature BCC parent phase transition temperature, the yield strength and uniform deformation ability of the alloy are improved.
It has achieved a balance between high strength and high uniform deformation ability, with yield strength reaching 800~1100MPa, tensile strength exceeding 900MPa, uniform elongation can reach 6%~18%, and fracture strain can reach 20%~35%, suitable for aerospace High temperature environment.
Smart Images

Figure CN119194203A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-strength and toughness ZrNbTa-based refractory high-entropy alloy and a preparation method thereof, and belongs to the technical field of metal materials. Background Art
[0002] High entropy alloys are usually composed of 5 or more main elements, and the molar fraction of each main element in the alloy is maintained between 5% and 35%. The content of secondary elements generally does not exceed 5%. High entropy alloys use a variety of metal elements in combination, selectively add and control the proportion according to the required performance requirements, thereby achieving the improvement of the mechanical properties of the alloy and the regulation of the physical properties. The mechanical properties exhibited by high entropy alloys, such as high strength and high toughness, have received widespread attention in the field of industrial manufacturing.
[0003] Refractory high entropy alloy refers to a high entropy alloy with refractory metal elements as the main element. The refractory metal elements mainly include metal elements with high melting points (>1650°C) such as Ti, Zr, V, Nb, Hf, Ta, and W. Refractory high entropy alloys can usually maintain high high temperature strength and hardness, and have good oxidation resistance and corrosion resistance. Many favorable properties make it possible to be used in key components in high temperature environments such as aerospace and energy fields, and it is considered to be a favorable candidate for the next generation of high temperature alloys. However, refractory high entropy alloys usually do not have the ability to deform uniformly at room temperature. CN115386774A discloses a ZrHfVNbTa-based refractory high entropy alloy, which improves the uniform deformation ability of the refractory high entropy alloy by deformation-induced martensitic phase transformation, but the alloy has a low yield strength (450MPa), which seriously limits its application. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a high-strength and tough ZrNbTa-based refractory high-entropy alloy and a preparation method thereof. By optimizing the composition of the alloy, the alloy has a higher modulus mismatch, and the microstructure is regulated to obtain a double BCC structure, thereby achieving both high strength and high uniform deformation capacity.
[0005] To achieve the above objectives, the technical solution of the present invention is as follows.
[0006] A high-strength and high-toughness ZrNbTa-based refractory high-entropy alloy, wherein the atomic percentage expression of the refractory high-entropy alloy is Zr a Nb b Ta c M d, M is one or more of Al, Fe, Co, Cr, Ni, Cu, Mg, Be, Si, C, O, N, B and rare earth elements, 10≤a≤50, 15≤b≤53, 17≤c≤60, 0≤d≤15, a≠b≠c, 50≤b+c≤80, c≥b / 2, and a+b+c+d=100; the high entropy alloy is a double BCC phase, and the modulus mismatch is ≥0.274.
[0007] Preferably, the double BCC phases are TaZr phase and TaNb phase respectively.
[0008] Preferably, 20≤a≤45, 25≤b≤50, 25≤c≤55, 0≤d≤5.
[0009] Preferably, 60≤b+c≤75.
[0010] Preferably, M is one or more of Al, Fe, Cr and Cu.
[0011] Preferably, the refractory high entropy alloy has a yield strength of 800-1100 MPa, a tensile strength of 900-1250 MPa, a uniform elongation of 6%-18%, and a fracture strain of 20%-35%.
[0012] A method for preparing the high-strength and tough ZrNbTa-based refractory high-entropy alloy of the present invention comprises the following steps:
[0013] With metal elements Zr, Nb, Ta and M as raw materials, alloying and smelting are first carried out in an inert protective gas atmosphere to obtain a refractory high entropy alloy ingot with uniform structure, and then the ingot is kept at 50-200°C below the high-temperature BCC parent phase transformation temperature for 12-24 hours and cooled to obtain a high-strength and toughness ZrNbTa-based refractory high entropy alloy.
[0014] Preferably, an arc melting furnace is used for alloying melting.
[0015] Preferably, the alloying smelting is performed 3 to 5 times.
[0016] Preferably, the inert protective gas is argon.
[0017] Beneficial Effects
[0018] The present invention provides a high-strength and tough ZrNbTa-based refractory high-entropy alloy. The alloy is characterized in that a large atomic size mismatch is generated by controlling the ratio of elements such as Zr, Nb, and Ta to promote spinodal decomposition, thereby obtaining a refractory high-entropy alloy with a dual-toughness BCC structure, and high uniform elongation is obtained by utilizing coordinated deformation of two phases. Meanwhile, the modulus mismatch of the high-entropy alloy is ensured to be above 0.27 by regulating the content of the high-modulus element Ta, so that the maximum uniform elongation of the refractory high-entropy alloy can reach above 30%, and the alloy has high tensile strength (the maximum tensile strength can exceed 1100 MPa), and the yield strength can reach above 950 MPa.
[0019] The present invention provides a method for preparing a high-strength and high-toughness ZrNbTa-based refractory high-entropy alloy. The preparation process of the refractory high-entropy alloy is simple, the raw materials are easy to obtain, and industrial production is easy to achieve, which is conducive to promoting the engineering application of refractory high-entropy alloys in the fields of aerospace, automobiles, advanced manufacturing, new energy, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The Zr prepared in Example 1 27 Nb 37 Ta 36 Optical micrograph of the grain boundaries of a refractory high entropy alloy.
[0021] Figure 2 The Zr prepared in Example 1 27 Nb 37 Ta 36 X-ray diffraction (XRD) spectrum of refractory high entropy alloy.
[0022] Figure 3 The Zr prepared in Example 1 27 Nb 37 Ta 36 Surface distribution diagram of energy spectrum (EDS) of refractory high entropy alloy.
[0023] Figure 4 The Zr prepared in Example 1 27 Nb 37 Ta 36 Engineering stress-strain curves of quasi-static tension of refractory high-entropy alloys. DETAILED DESCRIPTION
[0024] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.
[0025] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0026] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0027] In the following examples and comparative examples:
[0028] (1) The main reagent information used is shown in Table 1.
[0029] Table 1
[0030]
[0031] (2) Material preparation, performance testing and structural characterization
[0032] High vacuum arc melting-tumble casting system: produced by Shenyang Haozhiduo New Materials Preparation Technology Co., Ltd.
[0033] Metallographic structure analysis: The metallographic structure of the prepared refractory high entropy alloy was observed using a German Zeiss Axio observer A1m metallographic microscope; the material was first mounted using a hot mounting machine, then polished with 400#, 800#, 1200#, 2000#, 3000#, 5000#, and 7000# sandpaper in sequence, and then polished with a silica suspension. Finally, it was immersed in an etchant prepared with a volume ratio of 1:3:40 of 10% HF by mass, 65% to 68% HNO3, and H2O for 2s to 30s to prepare a sample for metallographic analysis.
[0034] Phase analysis: The X-ray diffraction spectrum of the high entropy alloy was determined using a D8 advance X-ray diffractometer from Bruker AXS, Germany. The instrument had a measurement scanning angle range of 20-100°, using Cu target Kα rays, an operating voltage of 40 kV, an operating current of 40 mA, a scanning speed of 0.2 sec / step, a step size of 0.02° / step, and a measurement angle error of less than 0.01°.
[0035] Element analysis: The HITACHI S4800 cold field emission scanning electron microscope (HFESEM) produced by Hitachi, Japan, was used to perform EDS energy spectrum analysis on the high entropy alloy to analyze the types of elements in different phase structures.
[0036] Quasi-static tensile mechanical properties test: According to the standard GB / T228.1-2010, a CMT4305 microcomputer electronic universal testing machine was used to conduct axial quasi-static tensile tests at room temperature, with a strain rate of 10 -3 s -1 The test specimen is a non-standard I-shaped piece with a thickness of 1.0mm, a width of 3.14mm, a parallel section length of 10mm, and a gauge length of 5mm: the acquisition of mechanical performance parameters such as tensile strength and uniform elongation are based on the engineering stress-strain curve, among which the tensile strength is the maximum engineering stress that the refractory high entropy alloy can bear, and the uniform elongation is the engineering strain value corresponding to the tensile strength of the refractory high entropy alloy load.
[0037] Example 1
[0038] The refractory high entropy alloy of this embodiment includes, by atomic percentage, 27% Zr, 37% Nb and 36% Ta.
[0039] The method for preparing the refractory high entropy alloy of this embodiment comprises the following steps:
[0040] Zr, Nb and Ta blocks with a purity of more than 99.9% were used as raw materials. The oxide scale on the surface of the single raw materials was first removed by grinding with a grinding wheel, and then ultrasonically cleaned with anhydrous ethanol. The raw materials were placed in an arc melting furnace in the order of low to high melting points according to the proportion of 27% Zr, 37% Nb and 36% Ta. The vacuum was drawn to 2.5×10 -3 Pa, and then fill with 0.6 atmospheres of argon gas for smelting. Before smelting, melt the Ti ingot to absorb oxygen, and then start the formal smelting. After one smelting is completed, wait for the furnace to cool before the next smelting. Before the next smelting, turn the ingot over, then melt the titanium ingot to absorb oxygen, and repeat the previous steps. Carry out arc melting 5 times in this way. Make sure the ingot is fully melted during each smelting. Add magnetic stirring during the third and fourth smelting to obtain Zr with uniform structure. 27 Nb 37 Ta 36 High entropy alloy ingot. Zr 27 Nb 37 Ta 36 The high temperature BCC parent phase transformation temperature of high entropy alloy is 1305℃.
[0041] The high entropy alloy ingot was sealed in a quartz tube filled with argon and heat-treated at 1250°C for 24 hours to obtain a dual-phase Zr 27 Nb 37 Ta 36 Refractory high entropy alloys.
[0042] Zr 27 Nb 37 Ta36 Refractory high entropy alloys are characterized by microstructure. Figure 1 The characterization results show that the alloy presents an equiaxed crystal structure, with coarse precipitates existing at the grain boundaries and within the grains, and the precipitates are continuously distributed.
[0043] Zr 27 Nb 37 Ta 36 Refractory high entropy alloys are subjected to phase analysis. Figure 2 The characterization results show that the alloy has a double BCC phase. Figure 3 From the EDS spectrum, we can see that the BCC1 phase is a TaZr-rich phase and the BCC2 phase is a TaNb-rich phase, both of which are tough phases.
[0044] Zr 27 Nb 37 Ta 36 Quasi-static tensile test of refractory high entropy alloys. Figure 4 The test results show that the alloy has a tensile strength of 1040MPa, a yield strength of 998MPa, a uniform elongation of 11.5%, and a fracture strain of 31.2%, showing obvious work hardening phenomenon.
[0045] Example 2
[0046] The refractory high entropy alloy of this embodiment includes, by atomic percentage, 45% Zr, 35% Nb and 25% Ta.
[0047] The method for preparing the refractory high entropy alloy of this embodiment comprises the following steps:
[0048] Zr, Nb and Ta blocks with a purity of more than 99.9% were used as raw materials. The oxide scale on the surface of the single raw materials was first polished with a grinding wheel, and then ultrasonically cleaned with anhydrous ethanol. The raw materials were placed in an arc melting furnace in the order of low to high melting points according to the proportion of 45% Zr, 35% Nb and 25% Ta. The vacuum was drawn to 2.5×10 -3 Pa, and then fill with 0.6 atmospheres of argon gas for smelting. Before smelting, melt the Ti ingot to absorb oxygen, and then start the formal smelting. After one smelting is completed, wait for the furnace to cool before the next smelting. Before the next smelting, turn the ingot over, then melt the titanium ingot to absorb oxygen, and repeat the previous steps. Carry out arc melting 5 times in this way. Make sure the ingot is fully melted during each smelting. Add magnetic stirring during the third and fourth smelting to obtain Zr with uniform structure. 45 Nb 35 Ta 25 High entropy alloy ingot. Zr 45 Nb 35 Ta 25The high temperature BCC parent phase transformation temperature of high entropy alloy is 1317℃.
[0049] The high entropy alloy ingot was sealed in a quartz tube filled with argon and heat treated at 1150°C for 12 hours to obtain a dual-phase Zr 45 Nb 35 Ta 25 Refractory high entropy alloys.
[0050] Zr 45 Nb 35 Ta 25 The microstructure of the refractory high entropy alloy was characterized. According to the characterization results, the alloy showed an equiaxed crystal structure, with coarse precipitates existing at the grain boundaries and in the grains, and the precipitates were continuously distributed.
[0051] Zr 45 Nb 35 Ta 25 The refractory high entropy alloy was subjected to phase analysis. According to the characterization results, the alloy has a double BCC phase, BCC1 phase is a TaZr-rich phase, and BCC2 is a TaNb-rich phase, and both phases are tough phases.
[0052] Zr 45 Nb 35 Ta 25 The refractory high entropy alloy was subjected to a quasi-static tensile test. According to the test results, the alloy had a tensile strength of 945 MPa, a yield strength of 895 MPa, a uniform elongation of 6.8%, and a fracture strain of 23.7%.
[0053] Example 3
[0054] The refractory high entropy alloy of this embodiment includes, by atomic percentage, 25% Zr, 25% Nb and 50% Ta.
[0055] The method for preparing the refractory high entropy alloy of this embodiment comprises the following steps:
[0056] Use Zr, Nb and Ta blocks with a purity of more than 99.9% as raw materials. First, use a grinding wheel to remove the oxide scale on the surface of the single raw materials, and then use anhydrous ethanol for ultrasonic cleaning. Place them in an arc melting furnace in a ratio of 25% Zr, 25% Nb and 50% Ta. When placing, place the raw materials in the crucible in the order of melting point from low to high. Vacuum to 2.5*10 -3Pa, and then fill with 0.6 atmospheres of argon gas for smelting. Before smelting, melt the Ti ingot to absorb oxygen, and then start the formal smelting. After one smelting is completed, wait for the furnace to cool before the next smelting. Before the next smelting, turn the ingot over, then melt the titanium ingot to absorb oxygen, and repeat the previous steps. Carry out arc melting 5 times in this way. Make sure the ingot is fully melted during each smelting. Add magnetic stirring during the third and fourth smelting to obtain Zr with uniform structure. 25 Nb 25 Ta 50 High entropy alloy ingot. Zr 25 Nb 25 Ta 50 The high temperature BCC parent phase transformation temperature of high entropy alloy is 1325℃.
[0057] The high entropy alloy ingot was sealed in a quartz tube filled with argon and heat-treated at 1200°C for 12 hours to obtain a dual-phase Zr 25 Nb 25 Ta 50 Refractory high entropy alloys.
[0058] Zr 25 Nb 25 Ta 50 The microstructure of the refractory high entropy alloy was characterized. According to the characterization results, the alloy showed an equiaxed crystal structure, with coarse precipitates existing at the grain boundaries and in the grains, and the precipitates were continuously distributed.
[0059] Zr 25 Nb 25 Ta 50 The refractory high entropy alloy was subjected to phase analysis. According to the characterization results, the alloy has a double BCC phase, BCC1 phase is a TaZr-rich phase, BCC2 is a TaNb-rich phase, and both phases are tough phases.
[0060] Zr 25 Nb 25 Ta 50 The refractory high entropy alloy was subjected to a quasi-static tensile test. According to the test results, the tensile strength of the alloy was 1140MPa, the yield strength was 1060MPa, the uniform elongation was 11.4%, and the fracture strain was 24.3%.
[0061] Example 4
[0062] The refractory high entropy alloy of this embodiment includes, by atomic percentage, 30% Zr, 36% Nb, 32% Ta and 2% Al.
[0063] The method for preparing the refractory high entropy alloy of this embodiment comprises the following steps:
[0064] Zr blocks, Nb blocks, Ta blocks and Al blocks with a purity of more than 99.9% were used as raw materials. The oxide scale on the surface of the single raw materials was first polished with a grinding wheel, and then ultrasonically cleaned with anhydrous ethanol. The raw materials were placed in an arc melting furnace in the order of low to high melting points according to the proportion of 30% Zr, 36% Nb, 32% Ta and 2% Al. The vacuum was drawn to 2.5×10 -3 Pa, and then fill with 0.6 atmospheres of argon gas for smelting. Before smelting, melt the Ti ingot to absorb oxygen, and then start the formal smelting. After one smelting is completed, wait for the furnace to cool before the next smelting. Before the next smelting, turn the ingot over, then melt the titanium ingot to absorb oxygen, and repeat the previous steps. Carry out arc melting 5 times in this way. Make sure the ingot is fully melted during each smelting. Add magnetic stirring during the third and fourth smelting to obtain Zr with uniform structure. 30 Nb 36 Ta 32 Al2 high entropy alloy ingot. Zr 30 Nb 36 Ta 32 The high temperature BCC parent phase transformation temperature of Al2 high entropy alloy is 1440℃.
[0065] The high entropy alloy ingot was sealed in a quartz tube filled with argon and heat treated at 1250°C for 12 hours to obtain a dual-phase Zr 30 Nb 36 Ta 32 Al2 refractory high entropy alloy.
[0066] Zr 30 Nb 36 Ta 32 The microstructure of Al2 refractory high entropy alloy was characterized. According to the characterization results, the alloy showed an equiaxed crystal structure, coarse precipitates existed at the grain boundaries and in the grains, and the precipitates were continuously distributed.
[0067] Zr 30 Nb 36 Ta 32 Phase analysis of Al2 refractory high entropy alloy was carried out. According to the characterization results, the alloy has double BCC phases, BCC1 phase is TaZr-rich phase, BCC2 is TaNb-rich phase, and both phases are tough phases.
[0068] Zr 30 Nb 36 Ta 32 The Al2 refractory high entropy alloy was subjected to a quasi-static tensile test. According to the test results, the alloy had a tensile strength of 1037 MPa, a yield strength of 835 MPa, a uniform elongation of 7.2%, and a fracture strain of 26.3%.
[0069] Comparative Example 1
[0070] On the basis of Example 1, the smelted alloy ingot was placed in a vacuum gas quenching furnace and kept at 1450°C for 6 hours. The other steps and conditions were the same as those in Example 1, and the solid solution Zr 27 Nb 37 Ta 36 Refractory high entropy alloys.
[0071] Zr 27 Nb 37 Ta 36 The microstructure of the refractory high entropy alloy was characterized. According to the characterization results, the alloy showed an equiaxed crystal structure, and no precipitated phase appeared at the grain boundaries and in the crystals.
[0072] Zr 27 Nb 37 Ta 36 The refractory high entropy alloy was subjected to phase analysis, and according to the characterization results, the alloy had a single-phase BCC structure.
[0073] Zr 27 Nb 37 Ta 36 The refractory high entropy alloy was subjected to a quasi-static tensile test. According to the test results, the tensile strength of the alloy was 840 MPa, the yield strength was 720 MPa, and the fracture strain was 4.8%.
[0074] Comparative Example 2
[0075] The refractory high entropy alloy of this comparative example includes, by atomic percentage, 15% Zr, 30% Nb and 55% Ta.
[0076] The preparation method of the refractory high entropy alloy of this comparative example comprises the following steps:
[0077] Zr, Nb and Ta blocks with a purity of more than 99.9% were used as raw materials. The oxide scale on the surface of the single raw materials was first removed by grinding with a grinding wheel, and then ultrasonically cleaned with anhydrous ethanol. The raw materials were placed in an arc melting furnace in the order of low to high melting points according to the proportion of 15% Zr, 30% Nb and 55% Ta. The vacuum was drawn to 2.5×10 -3 Pa, and then fill with 0.6 atmospheres of argon gas for smelting. Before smelting, melt the Ti ingot to absorb oxygen, and then start the formal smelting. After one smelting is completed, wait for the furnace to cool before the next smelting. Before the next smelting, turn the ingot over, then melt the titanium ingot to absorb oxygen, and repeat the previous steps. Carry out arc melting 5 times in this way. Make sure the ingot is fully melted during each smelting. Add magnetic stirring during the third and fourth smelting to obtain Zr with uniform structure. 15 Nb 30 Ta55 High entropy alloy ingot. Zr 15 Nb 30 Ta 55 The high temperature BCC parent phase transformation temperature of high entropy alloy is 1176℃.
[0078] The high entropy alloy ingot was sealed in a quartz tube filled with argon and heat-treated at 1100°C for 12 hours to obtain Zr 15 Nb 30 Ta 55 Refractory high entropy alloys.
[0079] Zr 15 Nb 30 Ta 55 The microstructure of the refractory high entropy alloy was characterized. According to the characterization results, the alloy showed an equiaxed crystal structure without obvious second phase.
[0080] Zr 15 Nb 30 Ta 55 The refractory high entropy alloy was subjected to phase analysis, and according to the characterization results, the alloy had a single-phase BCC structure.
[0081] Zr 15 Nb 30 Ta 55 The refractory high entropy alloy was subjected to a quasi-static tensile test. According to the test results, the tensile strength of the alloy was 620 MPa, the yield strength was 530 MPa, and the fracture strain was 3.7%.
[0082] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.
Claims
1. A high-strength and high-toughness ZrNbTa-based refractory high-entropy alloy, characterized in that: The atomic percentage expression of the refractory high entropy alloy is denoted as Zr a Nb b Ta c M d , M is one or more of Al, Fe, Co, Cr, Ni, Cu, Mg, Be, Si, C, O, N, B and rare earth elements, 10≤a≤50, 15≤b≤53, 17≤c≤60, 0≤d≤15, a≠b≠c, 50≤b+c≤80, c≥b / 2, and a+b+c+d=100; the high entropy alloy is a double BCC phase, and the modulus mismatch is ≥0.
274.
2. A high-strength and tough ZrNbTa-based refractory high-entropy alloy as claimed in claim 1, characterized in that: The double BCC phases are TaZr phase and TaNb phase respectively.
3. A high-strength and tough ZrNbTa-based refractory high-entropy alloy as claimed in claim 1, characterized in that: 20≤a≤45, 25≤b≤50, 25≤c≤55, 0≤d≤5.
4. A high-strength and tough ZrNbTa-based refractory high-entropy alloy as claimed in claim 1, characterized in that: 60≤b+c≤75.
5. A high-strength and tough ZrNbTa-based refractory high-entropy alloy as claimed in claim 1, characterized in that: M is one or more of Al, Fe, Cr, and Cu.
6. A high-strength and tough ZrNbTa-based refractory high-entropy alloy according to any one of claims 1 to 5, characterized in that: The refractory high entropy alloy has a yield strength of 800-1100 MPa, a tensile strength of 900-1250 MPa, a uniform elongation of 6%-18%, and a fracture strain of 20%-35%.
7. A method for preparing a high-strength and tough ZrNbTa-based refractory high-entropy alloy according to any one of claims 1 to 6, characterized in that: The method steps include: With metal elements Zr, Nb, Ta and M as raw materials, alloying and smelting are first carried out in an inert protective gas atmosphere to obtain a refractory high entropy alloy ingot with uniform structure, and then the ingot is kept at 50-200°C below the high-temperature BCC parent phase transformation temperature for 12-24 hours and cooled to obtain a high-strength and toughness ZrNbTa-based refractory high entropy alloy.
8. The method for preparing a high-strength and tough ZrNbTa-based refractory high-entropy alloy according to claim 7, characterized in that: An arc melting furnace is used for alloying melting.
9. The method for preparing a high-strength and tough ZrNbTa-based refractory high-entropy alloy according to claim 7, characterized in that: Alloying and melting are performed 3 to 5 times.
10. The method for preparing a high-strength and tough ZrNbTa-based refractory high-entropy alloy according to claim 7, characterized in that: The inert protective gas is argon.
Citation Information
Patent Citations
Multi-principal-element alloy containing BCC / B2 double-phase structure and preparation method of multi-principal-element alloy
CN113088784A
Refractory medium-entropy alloy and preparation method thereof
CN114134385A
TaMoZrTiAl system refractory high-entropy alloy with high toughness and double-BCC structure
CN116005059A
Methods of fabricating a refractory-metal article, and apparatuses for use in such methods
US20130092298A1
Niobium silicide-based alloy and method for producing same
WO2024181505A1
Cited By
High-density high-strength plasticity TaNbZr multiphase alloy and preparation method thereof
CN122542906A
